[PP.32.21] AN ANALYSIS OF HYPERTENSIVE MALE PATIENTS ADDRESSED TO A PRIMARY CARE PRACTICE. (September 2016) - Iancu, M.; Diaconu, C.; Dediu, G.; Balaceanu, L.; Matei, R.; Matei, D.
Abstract : Objective: The great majority of hypertensive patients are cared for in primary care. The objective of the study was to investigate the comorbidities of male hypertensive patients addressed to a primary care practice and to create a regression model with systolic blood pressure as dependent variable and other clinical and paraclinical factors that could have an influence on the blood pressure values. Design and method: The prospective study included 51 male patients with diagnosed arterial hypertension consecutively addressed for prescription refilling to a family medicine practice in 2015. We recorded the family and personal medical history, performed the clinical exam, laboratory tests (blood sugar, lipids), and ECG in every patient. The statistical analysis was made using the SAS system. Results: The epidemiological, clinical and paraclinical characteristics of the patients are described in Table 1. Half of the study group had over 50 years old and the BMI above 29 Kg/m2. 40% of the patients were smokers, 29% were diagnosed with type 2 diabetes, 10% had a family history of diabetes, and 27% had a family history of hypertension. All the patients were in sinus rhythm. 82% of the patients had dyslipidemia. 25% of the hypertensive patients had both diabetes and dyslipidemia. The Pearson Correlation Matrix showed a relationship between systolic blood pressure with BMI (11%), heart rate (35%), family history of diabetes (13%) and hypertension (12%), and smoking status (19%). Figure. No caption available. Conclusions: Almost 1/3 of male hypertensive patients in our study had diabetes. A large majority of hypertensive patients had dyslipidemia. We have found a significant relationship between systolic blood pressure values and BMI, heart rate, family history of diabetes and hypertension, and smoking status. The analysis of every-day practice may offer insights into the comorbidities of hypertensive patients, that should be addressed for a better control of all the cardiovascular risk factors.